Mitochondrial DNA Subhaplogroups L0a2 and L2a Modify Susceptibility to Peripheral Neuropathy in Malawian Adults on Stavudine Containing Highly Active Antiretroviral Therapy - Kampira, Elizabeth (JAIDS Journal of Acquired Immune Deficiency Syndromes, 2013)
BACKGROUND: Peripheral neuropathy (PN) is one of the main toxicities associated with stavudine. Genetic variants in mitochondrial DNA (mtDNA) haplogroups have been associated with increased risk of developing PN in European non-Hispanic and black patients on stavudine containing antiretroviral therapy (ART). We investigated mtDNA haplogroups and their role in susceptibility to stavudine-induced peripheral in Malawian patients on ART. METHOD: Two hundred and fifteen adults on stavudine containing regimens were recruited from the ART clinic at Queen Elizabeth Central Hospital, Blantyre, into a cross-sectional study to investigate the effects of genetic variants in mtDNA of individuals in relation to response to treatment. Patients were categorized according to whether or not they had developed PN after a minimum of 6 months on stavudine containing ART. Whole mtDNA coding regions of each patient were sequenced, and CD4 count, viral load, and creatinine were determined. The mtDNA variation was correlated with clinical characteristics. RESULTS: Fifty-three (25%) of the participants developed PN after starting stavudine containing ART. Mitochondrial DNA subhaplogroup L0a2 was independently associated with increased risk of PN in a multivariate model (odds ratio, 2.23; 95% confidence interval, 1.14 to 4.39; P = 0.019), and subhaplogroup L2a was independently associated with reduced risk of PN (odds ratio, 0.39; 95% confidence interval, 0.16 to 0.94; P = 0.036). CONCLUSIONS: Genetic variation in mtDNA confers differential risk of developing PN in patients on stavudine containing ART among Malawians.